Exploring Cultural Translation (Eurasian Research Bulletin, 2024)
Cultural translation plays a crucial role in fostering mutual understanding, enabling cross-cultural communication, and overcoming linguistic and cultural boundaries. This academic paper explores the complex field of cultural translation, examining its importance, difficulties, and transformative potential in the contemporary global environment.